2016
DOI: 10.1016/j.jval.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Country-Level Cost-Effectiveness Thresholds: Initial Estimates and the Need for Further Research

Abstract: BackgroundCost-effectiveness analysis can guide policymakers in resource allocation decisions. It assesses whether the health gains offered by an intervention are large enough relative to any additional costs to warrant adoption. When there are constraints on the health care system’s budget or ability to increase expenditures, additional costs imposed by interventions have an “opportunity cost” in terms of the health foregone because other interventions cannot be provided. Cost-effectiveness thresholds (CETs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
747
3
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(769 citation statements)
references
References 25 publications
9
747
3
10
Order By: Relevance
“…This guidance is in line with recent studies that have suggested that the WTP threshold should be much lower [66,67]. Since the country-level financing for malaria is often a ring-fenced amount of money, one alternative is to use resource allocation based on cost-effectiveness [68].…”
Section: Chapter 1 Introductionsupporting
confidence: 71%
“…This guidance is in line with recent studies that have suggested that the WTP threshold should be much lower [66,67]. Since the country-level financing for malaria is often a ring-fenced amount of money, one alternative is to use resource allocation based on cost-effectiveness [68].…”
Section: Chapter 1 Introductionsupporting
confidence: 71%
“…Commission on Macroeconomics and Health, 2001;Marseille et al, 2015;Bertram et al, 2016; Paulden et al, 2016;Pinto et al, 2016;. Mais recentemente descritos, os modelos de "estante de livros" (Culyer, 2016;Remme et al, 2016), fronteira de eficiência (Institute for Quality and Efficiency in Health Care, 2009) e eficiência média do sistema (Claxton et al, 2015;Woods et al, 2016) são alternativas ao uso de valores fixos de LCE.Sob uma perspectiva de custo de oportunidade, como o LCE indica aquelas tecnologias que são eficientes para incorporação, não é possível que o orçamento e o limiar sejam simultaneamente fixos. A ideia de implantação do princípio de custo de oportunidade é que, para a incorporação de novas tecnologias que impõe custos adicionais ao sistema, em um contexto de escassez de recursos, haverá deslocamento de tecnologias financiadas ou que esse recurso faltará em algum outro ponto do sistema.…”
unclassified
“…Commission on Macroeconomics and Health, 2001;Marseille et al, 2015;Bertram et al, 2016;Paulden et al, 2016;Pinto et al, 2016;. Mais recentemente descritos, os modelos de "estante de livros" (Culyer, 2016;Remme et al, 2016), fronteira de eficiência (Institute for Quality and Efficiency in Health Care, 2009) e eficiência média do sistema (Claxton et al, 2015;Woods et al, 2016) são alternativas ao uso de valores fixos de LCE.…”
unclassified
“…....................... 107 Tabela 24. Limiares de custo-efetividade em países selecionados, segundo metodologia do Centro para Economia da Saúde da Universidade de York (93) . (106) .…”
Section: Lista De Figurasunclassified
“…A primeira categoria de publicações avaliou a adoção de programa de rastreamento para mutação germinativa, em nível populacional, para indivíduos com algoritmo preditivo de risco para mutação ≥ 10% (99) ou etnia judaica Ashkenazi (95,98,102) . O segundo grupo de publicações avaliou a adoção de estratégias cirúrgicas preventivas para indivíduos reconhecidamente portadores de mutação germinativa em genes BRCA1/2 (88,92,93 Os objetivos do projeto principal relacionam-se ao reconhecimento do perfil genético de pacientes diagnosticadas com câncer de ovário, ao desenvolvimento de questionário para detecção de fatores associados, à estimativa de risco para mutação em genes BRCA1/2 mediante aplicação de algoritmos de risco e à avaliação de custoefetividade de testes genéticos. Trata-se de um estudo transversal que incluiu amostra de cem pacientes portadoras de câncer de ovário em seguimento em um hospital público de ensino, independentemente de idade e história familiar de neoplasia maligna (11) .…”
Section: Paísunclassified